Rancang Bangun Pembersih Kandang Anak Ayam Menggunakan Konveyor Berbasis Internet Of Things - Ailillatur Rosadi; Jati Widyo Leksono; Nailul Izzati; Imamatul Ummah (Universitas Darul Ulum, 2024)
The cleanliness of chick coops is crucial, especially in large-scale poultry farms, as it directly affects the health and well-being of the chicks. Manual cleaning of coops can be very tiring and inefficient. This study aims to design and implement an automatic chick coop cleaning system based on a conveyor belt equipped with a DHT22 temperature sensor and an MQ-135 ammonia sensor, using an ESP32 module for automatic control and Internet of Things (IoT) integration. The results show that the system operates well, with temperature measurement errors ranging from 0% to 3,10% and ammonia measurements ranging from 7 to 40,00 ppm. To improve reliability, it is recommended to use sensors with higher accuracy and add an offline mode so the system can still function without an internet connectio